Corruption in State contracts: The construction club nefaste in Peru - Hennings Otoya, Julio Alberto (2020)
The study addresses the problem of corruption in the construction sector of Peru, focusing on illegal practices carried out in the case known as the "Construction Club", an organization of executives of private companies, that using corrupt practices colluded with officials and high government authorities, managed to hoard and overvalue the public works tendered by the State for an estimated period that would exceed 20 years, thereby increasing the cost of public projects and affecting the competitiveness of the sector, among other serious inconveniences. The article describes the main facts, with the objective of analyzing the problem of corruption in the contracting of works of the Peruvian State, reflecting on its causes and the effect it produces on the efficiency of the market in that sector. Suggestions and recommendations that could mitigate the risk in such operations in the State sector were offered. In the study, the documentary review, market theories and hypotheses, expert interviews and the analysis of the facts were used.